Ваша красота в здоровье! - Свищева Тамара Яковлевна (Таинственный убийца, 2001)
Экземпляры: КХ (20050114) / Инвентарный номер: 1052590 / Цена: 62.25 / Сис.шифр: 51.204 / Авт.знак: С 24 / ГРНТИ: 76 / ББК: 51.204